Digital Transformation of Toko Madi MSME's: Improving Business in the Digital Era - Tjandinegara, Tiffany; Fanilam Putri, Elma; Christina Chandra, Nova; Christina Chandra, Novi; Nasir, Arnold; Suardi, Citra (INTRO : Journal Informatika dan Teknik Elektro, 2024)
MSMEs, which stands for Micro, Small, Medium Enterprises, have a number of problems, including the lack of use of technology in business development and obstacles in accessing market information. Digital transformation allows MSMEs to utilize technology in developing their businesses, increasing operational efficiency and better accessing market information. This research aims to utilize digital transformation in entrepreneurship in the digital era and its application in the business development of Toko Madi. This research uses a mobile application development approach to create a digital platform for MSMEs "Toko Madi." This application includes a login page, profile settings, item catalog, purchase history, and management features for shop owners, such as stock management, shipping, and sales data. It is hoped that the results of this research can increase the income of "Toko Madi" MSMEs by enabling them to reach customers outside the city and take advantage of the benefits of digital transformation. This digital transformation includes the process of digitizing the business, utilizing mobile applications, and using analytical tools to increase efficiency, productivity, and innovation. In conclusion, digital transformation is an important step for MSMEs in facing challenges and competing in an increasingly competitive global market. With this mobile application, MSMEs can increase their online presence, manage their business better, and adapt to dynamic changes in the digital era.